WELDING CHARACTERISTICS OF SECONDARY ALUMINUM ALLOYS - O. V. Lutova (Литьë и металлургия, 2013)
It is shown that netal of welded connections of AK9M2 alloy is not only not inferior to the base metal as regards durability, elongation and hardness but even exceeds its characteristies..